The melancholy void: lyric and masculinity in the age of Góngora - Valencia, Felipe (New Hispanisms, 2021)
Introduction: The melancholy and masculinist poetics in early modern Spanish lyric -- The gendering of lyric and epic in Alonso de Ercilla's La Araucana, 1569-1590 -- The Apollonian and Orphic masculinity of Fernando de Herrera's heroic lyric in Algunas obras, 1582 -- Feminine voice and masculinist aims in Miguel de Cervante's La Galatea, 1585 -- Between Liuvigild and Ingund in Juan de Arguijo's Versos, 1612 -- "El melancólico vacío" : the origins and fate of lyric according to Luis de Góngora's Fábula de Polifemo y Galatea, 1612, and Soledades, 1613-1617.